UPAYA END CHILD PROSTITUTION IN ASIA TOURISM (ECPAT) DALAM MENGATASI EKPLOITASI ANAK DI KAMBOJA 2009-2015 - Nusantara, Nugraha; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research aims to find out the effort made by ECPAT in dealing with the issues of Commercial Sexual Exploitation of Children (CSEC) in Cambodia. As one of the countries with low economic levels in Southeast Asia. Many Children fall into CSEC and Cambodia is a sex tourism destination by foreign tourists. To address this issue, Cambodia government take actions by cooperating with ECPAT which is International Organization non-governmental whose focus is to eliminate CSEC. ECPAT has several effort made in CSEC cases. This research use a pluralism perspective which believe that states are not the only actor in international world and Role theory, The research method used in this study is a Qualitative method, the data collection technique used is the Library research technique.The result of this research is ECPAT have been doing some efforts to eliminate CSEC. The effort taken was to hold YPP, in collaboration with The Body Shop in conducting the campaign and ECPAT in collaboration with the Cambodian Ministry of Tourism, held LokalkaryaKeywords: ECPAT, Effort, Cambodia, CSEC (Commercial Sexual Exploitation of Children)